Update on pregnancy-associated venous thromboembolism - Arielle L. Langer; Nathan T. Connell (Thrombosis Update, 2022)
Venous thromboembolism (VTE) is a major cause of morbidity and mortality in pregnancy. Multiple physiologic changes in pregnancy contribute to the increased risk of VTE. VTE in this setting presents unique challenges for diagnosis and management. Evidence-based diagnostic practices include limiting D-dimer testing, reliance on ultrasound and V/Q scan when possible, and counseling patients and their families on the safe use of CT imaging of the chest when needed. Anticoagulation primarily relies on low molecular weight heparin, but unfractionated heparin and fondaparinux may also be used when needed. Warfarin is a known teratogen and induces an anticoagulant effect in the fetus. Safety data for other anticoagulants is lacking. Thrombolysis should be limited to patients with significant hemodynamic compromise due to the high risk of bleeding with this intervention. For individuals with prior VTE who are no longer on anticoagulation, prophylactic anticoagulation is usually reserved for those with prior estrogen-associated or unprovoked VTE. Future prophylaxis can be limited to additional pregnancies in most individuals. Future exposure to exogenous estrogen should be avoided. Prophylactic anticoagulation on the basis of heritable thrombophilias without a personal history of VTEs is not usually indicated, as risks of bleeding and interference with the use of neuraxial anesthesia outweigh benefits in most instances. Therefore, primary prophylaxis should be limited to only the high risk genotypes.